Faith-Base Communities (FBCs) in Ecological Counseling (EC) to Promote Well-Being (WB) in Millenial Era - Anwar, Moh Khoerul; Ningsih, Ruly (Counsellia: Jurnal Bimbingan dan Konseling, 2019)
Well-being are the populer issues among academic researchers. This issues related to any change in millennial era. This article aimed to explain how faith-base community (FBCs) could promote well-being (WB) in millennial era. Data gathered by literature study included journal articles and books. The results of the study indicated  that the efforts to promote well-being wellbeing could be done with collaborative efforts of counselors with faith communities. There were many evidence showed that faith-base community (FBCs) could  be important collaborators to deliver a mission of morality and bring the mission of promoting psychological well-being (WB) in society. The implication of the study that counselors had to have the ecological competences that could lead the counselor to the multicultural thinking paradigm, as well as the development of the systemic intervention framework.Kesejahteraan psikologis merupakan kajian yang populer dikalangan peneliti.  Kajian ini berkatian dengan beberapa perubahan di era milenial.  Artikel ini bertujuan untuk menjelaskan mengenai komunitas beragama yang dapat berfungsi sebagai alternative untuk mempromosikan kesejahteraan psikologis di era milenial.  Data yang diperoleh dalam penulisan artikel ini dilakukan dengan melakukan kajian literatur.  Hasil kajian ini menunjukkkan adanya beberapa bukti bahwa komunitas beragama dapat menjadi kolaborator penting dalam menyampaikan misi moralitas dan misi tercapainya kesejahteraan psikologis di masyarakat.  Implikasi temuan ini terhadap profesi konseling yaitu agar konselor memiliki komptensi ekologis yang akan membantunya memiliki paradigma multukultural, maupun pengembangan kerangka intervensi sistemik.